Study of cyclic adenosine monophosphate microdomains in cells. - Mongillo, M; Terrin, A; Evellin, S; Lissandron, V; Zaccolo, M (2005)
Cyclic adenosine monophosphate (cAMP) controls the physiological response to many diverse extracellular stimuli. To maintain signal specificity, cAMP-mediated signaling is finely tuned by means of a complex array of proteins that control the spatial and temporal dynamics of the second messenger within the cell. To unravel the way a cell encodes cAMP signals, new biosensors have recently been introduced that allow imaging of the second messenger in living cells with high spatial resolution. The more recent generation of such biosensors exploits the phenomenon of fluorescence resonance energy transfer between the green fluorescent protein- tagged subunits of a chimeric protein kinase A, as the way to visualize and measure the dynamic fluctuations of cAMP. This chapter describes the molecular basis on which such a genetically encoded cAMP sensor relies and the tools and methods required to perform cAMP measurements in living samples.